Incidence Rates of Tuberculosis among Children and Adolescents Living in Areas Most Affected by the Chernobyl Disaster - Gorbach, Larissa (J Health Pollut, 2016)
BACKGROUND. The Chernobyl accident has attracted the attention of healthcare experts all over the world due to the unprecedented scale of damage the disaster inflicted upon human health. OBJECTIVES. To examine incidence rates of tuberculosis and patterns among children and adolescents living in areas most affected by the Chernobyl disaster between 2004 and 2014. METHODS. The tuberculosis incidence rate was calculated per 100,000 people. Incidence dynamics were traced for the period 2004 to 2014 and average rates were measured. Average incidence rates were calculated for different age groups, including 0–4 years, 5–9 years, 10–14 years, and 15–19 years, as well as the total value for all those between 0–19 years of age. Average incidence rates were estimated for tuberculosis, pulmonary tuberculosis and extrapulmonary tuberculosis. A comparative analysis of incidence rates of tuberculosis in areas more and less affected by the Chernobyl disaster was conducted. To avoid gender and age disparities among the population in the two different study areas, a method of direct standardization was applied. RESULTS. Tuberculosis incidence rates showed identical patterns among the population across all areas in this region. At the same time, the incidence rates of tuberculosis, pulmonary tuberculosis, and extrapulmonary tuberculosis were higher among children and adolescents living in the most affected areas in comparison to those living in less affected areas. CONCLUSION. The results do not allow us to conclude whether radioactive pollution has a direct impact on incidence of tuberculosis among children and adolescents in the most radioactively contaminated areas. The author believes that the higher incidence rates of tuberculosis in the most affected areas are conditioned by a set of negative factors that have a pernicious influence on the general health of the population, and on the health of children and adolescents in the areas most affected by the Chernobyl disaster.